PENGARUH GAYA HIDUP, BRAND IMAGE,DAN PERSEPSI KUALITAS TERHADAPKEPUTUSAN PEMBELIAN IPHONE SECONDPADA GENERASI Z DI KOTA DENPASAR - Ni Kadek Sintya Devi; I Gusti Ayu Imbayani; Made Pradnyan Permana Usadi (Journal Research of Management, 2026)
The increasing number of smartphone users has also influenced people's preference patterns for brands, especially among Generation Z. Although the price of the iPhone is known to be quite high, this device remains highly sought after, even in second-hand condition. This study aims to determine the influence of lifestyle, brand image and perceived quality on purchasing decisions. The research method used is quantitative. The population used are consumers who have purchased iPhones, born between 1997 and 2012 and domiciled in Denpasar City and a sample of 150 people. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Coefficient of Determination, F Test and t Test. The results of the study obtained indicate that lifestyle, brand image and perceived quality each have a positive and significant influence on purchasing decisions. Suggestions in this study are that second-hand iPhone sellers are expected to always offer iPhone products that have a good appearance and features, always carry out detailed checks on iPhone products, always provide product specification information honestly and according to actual conditions.